2021
DOI: 10.3390/ma14154073
|View full text |Cite
|
Sign up to set email alerts
|

1T-MoS2 Coordinated Bimetal Atoms as Active Centers to Facilitate Hydrogen Generation

Abstract: Anchoring single metal atoms has been demonstrated as an effective strategy to boost the catalytic performance of non-noble metal 1T-MoS2 towards hydrogen evolution reaction (HER). However, the dual active sites on 1T-MoS2 still remain a great challenge. Here, first-principles calculations were performed to systematically investigate the electrocatalytic HER activity of single and dual transition metal (TM) atoms bound to the 1T-MoS2 monolayer (TM@1T-MoS2). The resulted Ti@1T-MoS2 exhibits excellent structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Specifically, the metallic 1T-MoS 2 nanosheet exhibits high conductivity, low cost, and intrinsic HER activity. , It performs well as an electrocatalyst toward HER in acidic solution. , The sulfur on the outer surface of 1T-MoS 2 catalyzes the generation of hydrogen from free protons, like those generated from the water splitting in the OER. By anchoring single Pd atoms, our previous DFT results found that the S atom near Pd becomes more activated for HER . Also, the experimental and theoretical studies of Lau et al demonstrated that the immobilization of single Pd atoms on the 1T-MoS 2 basal plane can greatly promote the proton reduction step from water splitting to produce hydrogen and render it non-rate-limiting, further improving the kinetic rate and efficiency of 1T-MoS 2 for HER.…”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Specifically, the metallic 1T-MoS 2 nanosheet exhibits high conductivity, low cost, and intrinsic HER activity. , It performs well as an electrocatalyst toward HER in acidic solution. , The sulfur on the outer surface of 1T-MoS 2 catalyzes the generation of hydrogen from free protons, like those generated from the water splitting in the OER. By anchoring single Pd atoms, our previous DFT results found that the S atom near Pd becomes more activated for HER . Also, the experimental and theoretical studies of Lau et al demonstrated that the immobilization of single Pd atoms on the 1T-MoS 2 basal plane can greatly promote the proton reduction step from water splitting to produce hydrogen and render it non-rate-limiting, further improving the kinetic rate and efficiency of 1T-MoS 2 for HER.…”
Section: Results and Discussionmentioning
confidence: 95%
“…By anchoring single Pd atoms, our previous DFT results found that the S atom near Pd becomes more activated for HER. 43 Also, the experimental and theoretical studies of Lau et al 22 demonstrated that the immobilization of single Pd atoms on the 1T-MoS 2 basal plane can greatly promote the proton reduction step from water splitting to produce hydrogen and render it non-rate-limiting, further improving the kinetic rate and efficiency of 1T-MoS 2 for HER. In concert with the newfound OER and ORR catalytic capability on the Pd site, Pd@1T-MoS 2 is a promising trifunctional electrocatalyst for HER, OER, and ORR.…”
Section: Resultsmentioning
confidence: 99%
“…It will not only address human daily needs but also enhance the energy security of all countries and reduce international conflicts caused by the fossil energy crisis, thereby promoting harmonious global development, enhancing sustainability and reducing pollution [1][2][3]. Ultrathin MoS 2 nanosheet is a typical material in transition metal sulfide systems attracting extensive attention in recent years, possessing superior structural and photocatalytic properties, and becoming a substitute for platinum in highly active hydrogen production reactions [4,5].…”
Section: Introductionmentioning
confidence: 99%